2021
DOI: 10.1371/journal.pone.0252393
|View full text |Cite|
|
Sign up to set email alerts
|

Optimizing sowing date for peanut genotypes in arid and semi-arid subtropical regions

Abstract: Peanut (Arachis hypogea L.) is an important nut crop extensively grown in rainfed regions of Pakistan. The crop requires low inputs; thus, could grow successfully under diverse environmental conditions. Due to pegging ability, peanut grows aggressively in sandy and sandy-loam soils. However, it has not introduced to Thal region of southern Punjab, Pakistan. A two-year field experiment was conducted to optimize sowing dates for two peanut genotypes (‘BARI-2016’ and ‘NO-334’) in Thal region (Layyah). Similarly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Drought stress reduces plant height, shoot dry weight and root dry weight. Drought stress and salinity stress decreased the germination rate and plant growth in various crops ( Farooq et al, 2009 , Awari and Mate, 2015 , Hussain et al, 2016 , Egamberdieva and Jabborova, 2013 ; Egamberdieva et al, 2016 , Egamberdieva et al, 2017 , Jabborova et al, 2020c , Sheteiwy et al, 2021 , Ijaz et al, 2021 ). Similarly, Mueller et al (2019) reported that okra growth and the total dry weight of okra was reduced by drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…Drought stress reduces plant height, shoot dry weight and root dry weight. Drought stress and salinity stress decreased the germination rate and plant growth in various crops ( Farooq et al, 2009 , Awari and Mate, 2015 , Hussain et al, 2016 , Egamberdieva and Jabborova, 2013 ; Egamberdieva et al, 2016 , Egamberdieva et al, 2017 , Jabborova et al, 2020c , Sheteiwy et al, 2021 , Ijaz et al, 2021 ). Similarly, Mueller et al (2019) reported that okra growth and the total dry weight of okra was reduced by drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…The variations of sowing dates interact with climatic conditions, in particular, during critical stages, leading to affected peanut growth and yield (Caliskan et al., 2008; Ijaz et al., 2021; Sarkees., 2015). Matching crop phenology to the duration of favorable conditions by selecting the most appropriate sowing dates to avoid stress is crucial for maximizing yield (Caliskan et al., 2008; Zanon et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Matching peanut to phenology and climate conditions by selecting the most suitable sowing dates to avoid stress (i.e., temperature and rainfall extremes) is of great importance to maximize yield (Foyer et al., 2016; Lobell & Gourdji., 2012; Meena et al., 2015a; Tian et al., 2019). For example, the highest yield was obtained with an early sown crop (April 10), and yield decreased by 40% when sowing was delayed by 20 days in arid and semi‐arid regions (Ijaz et al., 2021). Late sowing leads to unfavorable day length, and increases vegetative growth by extending the photoperiod, as well as decreasing reproductive growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sowing wheat crops in borondeficient soil leads to grains sterility in the wheat crop [18]. Similarly, the boron deficiency leads towards cell wall breakdown, slowed proton pump, ATPs development, lower photosynthetic productivity, and declined electron transport chain functioning [19,20]. Boron also affects several biological functions in plants, including the synthesis of cell walls, proteins, the metabolism of carbohydrates and nucleic acids and cell wall enlargements, and assimilates translocation [21].…”
Section: Introductionmentioning
confidence: 99%